A 60-year-old male presented with left-sided weakness and difficulty in speech (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
This article has no abstract. The first 100 words appear below:A 60-year-old male presented with weakness of the left side of the body followed by a sudden fall on the ground while working in the field, with difficulty in speech for 03 months. Weakness was sudden in onset which involved left upper and lower limbs with the inability to move the left side of the body and difficulty in walking. The patient also noticed that there was a deviation of the face towards the right side associated with dribbling of food with difficulty in speech but can follow the command with difficulty. There was also urinary incontinence for the same duration, but the bowel movement was normal.